Performance Improvement of Vertical Channel Indium–Gallium–Zinc Oxide Thin-Film Transistors Using Porous MXene Electrode - Wanqiang Fu; Qizhen Chen; Peng Gao; Linqin Jiang; Yu Qiu; Dong-Sing Wuu; Ray-Hua Horng; Shui-Yang Lien (Energies)
The surface morphology of porous source electrodes plays a significant role in the performance of vertical channel indium–gallium–zinc oxide thin-film transistors (VC-IGZO-TFTs). This study systematically investigates the properties of porous MXene-based source electrodes and their impact on VC-IGZO-TFTs fabricated with varying MXene concentrations. As the MXene concentration increases, both the sheet resistance and porosity of the electrodes decrease. VC-IGZO-TFTs based on a 3.0 mg/mL MXene concentration exhibit optimal electrical performance, with a threshold voltage (Vth) of 0.16 V, a subthreshold swing (SS) of 0.20 V/decade, and an on/off current ratio (Ion/Ioff) of 4.90 × 105. Meanwhile, the VC-IGZO-TFTs exhibit excellent electrical reliability and mechanical stability. This work provides a way to analyze the influence of sheet resistance and porosity on the performance of VC-IGZO-TFTs, offering a viable approach for enhancing device efficiency through porous MXene electrode engineering.